Characteristics Of Islamic Education Leadership: Literature Review - Tri Na'imah,; Ahmad Muhibbin, (Technium Social Sciences Journal, 2020)
Leadership and management are different concepts, but both can be collaborated to achieve active organizational goals. Leadership theories have been developed, but there are still gaps in the idea of leadership when applied in school organizations. Leadership in an Islamic perspective is not just a social contract between the leader and his subordinates but also a psychological contract between the leader and God. Leadership in Islam is a mandate, namely a psychological agreement between a leader and his assistants that there will be fair treatment, protection, and guidance for subordinates. Therefore the Islamic values that must color the work of Islamic leaders in educational organizations are sincere, shura, ikhtilaf, maslaha, amar ma'ruf nahi munkar, husba, and tafakur.